2008
DOI: 10.1136/sti.2007.026039
|View full text |Cite
|
Sign up to set email alerts
|

Spousal sexual violence and poverty are risk factors for sexually transmitted infections in women: a longitudinal study of women in Goa, India

Abstract: Socially disadvantaged women are at increased risk of STI in this population. Sexual intercourse outside marriage was rarely reported in this population, and women are at risk of becoming infected within marriage, especially those with sexual violence. This highlights the vulnerabilities of socially disadvantaged married women in India, and the need for healthcare professionals to screen STI patients for violence, and provide the necessary support. The results also stress the importance of effectively diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 36 publications
2
46
0
2
Order By: Relevance
“…Although age group of women was not significantly associated with STI risk (in model 2), that prevalence of STI or STI symptoms was highest among younger (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) women cannot be ignored. This finding could imply that younger women are more likely to be economically dependent on their partners, and less likely to leave a sexually risky or abusive relationship (29,33), or that they are less likely to enquire about their husbands previous or current sexual partners leaving them more vulnerable to infection (29).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Although age group of women was not significantly associated with STI risk (in model 2), that prevalence of STI or STI symptoms was highest among younger (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) women cannot be ignored. This finding could imply that younger women are more likely to be economically dependent on their partners, and less likely to leave a sexually risky or abusive relationship (29,33), or that they are less likely to enquire about their husbands previous or current sexual partners leaving them more vulnerable to infection (29).…”
Section: Discussionmentioning
confidence: 89%
“…Fear instilled by partner violence impairs women's ability to assess risk and interacts with their sexual decision making processes (2,6,9,17,18). Violence reduces women's ability to engage in safe sexual practices such as being able to refuse sex or to negotiate condom use, and this is particularly so in societies where high gender inequalities and social disadvantage exist (5,7,8,19,20). Further, factors such as poverty and barriers to education and employment opportunities, both reinforce and are reinforced by gender inequalities and serve to keep women and girls dependent upon their male partners (8,20).…”
Section: Pathways To Sti Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggests that effective screening and treatment of men is required for safe sex within marriage. 30 An urgent need is felt in Goa for the improvement of maternal health by partnering with private sector, effective provision of cash transfer to the pregnant women, and monitoring of public health facilities for reducing the financial distress among women.…”
Section: Nutritional Status and Anaemiamentioning
confidence: 99%
“…2 Several Interventional and national cross-sectional studies have shown the prevalence of violence, its risk factors and consequences on the overall health of women. [3][4][5][6][7][8][9][10][11][12][13][14] Very few qualitative studies discussed the relationship dynamics between the abusive husband and wife. [15][16][17][18][19][20] Studies from developing countries demonstrated that the women experienced a conflict of emotions and developed coping mechanisms.…”
Section: Introductionmentioning
confidence: 99%